2008
DOI: 10.1529/biophysj.107.119636
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Orientation of the C-Terminus of LRAP

Abstract: Amelogenin is the predominant protein found during enamel development and is thought to be the biomineralization protein controlling the unique elongated hydroxyapatite crystals that constitute enamel. The secondary structure of biomineralization proteins is thought to be important in the interaction with hydroxyapatite. Unfortunately, very little data are available on the structure or the orientation of amelogenin, either in solution or bound to hydroxyapatite. The C-terminus contains the majority of the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
92
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 67 publications
9
92
0
Order By: Relevance
“…15 It conserves the end terminals of the native protein, specifically the hydrophilic residues of the C-and inner N-termini that interact with HAP to direct mineral growth and for mineral binding. 16,17 Since interaction of the charged residues with the crystal surface plays a vital role in the biomineralization process, [18][19][20] LRAP proves to be an excellent model substitute for the full-length amelogenin in eliciting details about the secondary structure and orientation of the peptide at the apatite interface. 16,21,22 Although previous studies suggested that LRAP is a HAP crystal growth inhibitor, 15 current studies indicate that it may have an important function in promoting enamel mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…15 It conserves the end terminals of the native protein, specifically the hydrophilic residues of the C-and inner N-termini that interact with HAP to direct mineral growth and for mineral binding. 16,17 Since interaction of the charged residues with the crystal surface plays a vital role in the biomineralization process, [18][19][20] LRAP proves to be an excellent model substitute for the full-length amelogenin in eliciting details about the secondary structure and orientation of the peptide at the apatite interface. 16,21,22 Although previous studies suggested that LRAP is a HAP crystal growth inhibitor, 15 current studies indicate that it may have an important function in promoting enamel mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Mammals DMP1 4.0 CD, DLS, FTIR, SAXS (Gericke et al, 2010;He et al, 2003aHe et al, , 2003b DPP 2.8 CD, NMR, SAXS (Cross et al, 2005;Evans et al, 1994;Fujisawa & Kuboki, 1998;George & Hao, 2005;He et al, 2005b;Lee et al, 1977) BSP 4.1 CD, NMR, SAXS (Fisher et al, 2001;Tye et al, 2003Tye et al, , 2005Wuttke et al, 2001) OPN 4.4 CD, NMR, FTIR (Fisher et al, 2001;Gorski et al, 1995) amelogenin 6.6 CD, NMR (Buchko et al, 2010;Delak et al, 2009b;Ndao et al, 2011;Shaw et al, 2008) statherin 8.0 CD, NMR (Long et al, 2001;Naganagowda et al, 1998;Raj et al, 1992) lithostathine 5.7 CD (Gerbaud et al, 2000) Haliotis rufescens AP7 5.2 CD, NMR (Kim et al, 2004(Kim et al, , 2006aMichenfelder et al, 2003;Wustman et al, 2004) Atrina rigita Asprich 2.7-3.5 CD, NMR (Collino et al, 2006;Delak et al, 2009aDelak et al, , 2008Kim et al, 2008;Ndao et al, 2010) Procambrus clarkii CAP-1 3.9 CD (Inoue et al, 2007) Strongylocentrotus purpuratus SM50 10.8 CD, NMR (Xu & Evans, 1999;Zhang et al, 2000) PM27 8.1 CD, NMR Danio rerio Stm 4.1 CD, gel filtration (Kaplon et al, 2008(Kaplon et al, , 2009 Table 1. IDPs involved in biomineralization of calcium carbonate and phosphate for which a disordered structure has been confirmed...…”
Section: Protein Pi Methods Referencementioning
confidence: 99%
“…LRAP, like amelogenin (e.g., rH175), forms nanospheres, as shown for fluoroapatite (Habelitz et al, 2006) or surfactant-coated gold surfaces (Tarasevich et al, 2010), and appears to interact with hydroxyapatite through its C-terminus (Shaw et al, 2004), although this domain is not solely responsible for mineral binding (Shaw et al, 2008). LRAP is also processed during secretory amelogenesis by enamelysin, resulting in the removal of 16 C-terminal amino acids, and by kallikrein-4 during the maturation stage (Nagano et al, 2009).…”
mentioning
confidence: 99%